Sound Images of the Ocean in Research and Monitoring - Wille, Peter (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Ocean acoustics comprises a key subfield of research, providing indispensable tools for the exploration of the seafloor, other underwater formations and processes. Sound Images of the Ocean employs 400 sound images, contributed by 120 author/marine experts from 22 nations, to create a comprehensive overview of acoustic imaging applications in the sea. This remarkable ensemble spans fields of geophysical research, off-shore industrial and economic activities, national surveillance, and protection of the ocean and continental shelves. Written to be accessible to professionals in diverse related fields, the concise accompanying explanations of the complex relationships revealed by the images strive to condense the results into the essential "message." For readers, this remarkable atlas develops an interdisciplinary understanding of underwater acoustics and its diagnostic capabilities to visualize in detail the two thirds of the surface of the globe otherwise hidden from view.